Combined Culture-Based and Culture-Independent Approaches Provide Insights into Diversity of Jakobids, an Extremely Plesiomorphic Eukaryotic Lineage - Pánek, Tomáš; Táborský, Petr; Pachiadaki, Maria G.; Hroudová, Miluše; Vlček, Čestmír; Edgcomb, Virginia P.; Čepička, Ivan (Frontiers in Microbiology, 2015)
We used culture-based and culture-independent approaches to discover diversity and ecology of anaerobic jakobids (Excavata: Jakobida), an overlooked, deep-branching lineage of free-living nanoflagellates related to Euglenozoa. Jakobids are among a few lineages of nanoflagellates frequently detected in anoxic habitats by PCR-based studies, however only two strains of a single jakobid species have been isolated from those habitats. We recovered 712 environmental sequences and cultured 21 new isolates of anaerobic jakobids that collectively represent at least ten different species in total, from which four are uncultured. Two cultured species have never been detected by environmental, PCR-based methods. Surprisingly, culture-based and culture-independent approaches were able to reveal a relatively high proportion of overall species diversity of anaerobic jakobids - 60 % or 80 %, respectively. Our phylogenetic analyses based on SSU rDNA and six protein-coding genes showed that anaerobic jakobids constitute a clade of morphologically similar, but genetically and ecologically diverse protists – Stygiellidae fam. nov. Our investigation combines culture-based and environmental molecular-based approaches to capture a wider extent of species diversity and shows Stygiellidae as a group that ordinarily inhabits anoxic, sulfide- and ammonium-rich marine habitats worldwide.